Implementasi Pasal 17 Perda Disabilitas Gorontalo dalam Pendidikan Inklusif di Desa Bongo - M Hubaib, Siti Syukriyah; Zamroni Abdussamad; Mohamad Hidayat (Diktum: Jurnal Ilmu Hukum, 2026)
Gorontalo Provincial Regulation Number 4 of 2023 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities mandates inclusive education through Article 17 as an effort to provide equal educational opportunities. This study aims to analyze the juridical position of Article 17 as a legal basis for fulfilling the educational rights of persons with disabilities in Bongo Village, Batudaa Pantai District, Gorontalo Regency, and to identify gaps between normative mandates and field implementation. Using empirical legal research with a qualitative approach, data were collected through in-depth interviews with the Village Head, the Principal of SDN 03 Batudaa Pantai, and a parent of a student with disabilities, as well as through documentation studies. The findings indicate that Article 17 holds a normatively strategic position, aligning with national regulations and international human rights standards. However, implementation in Bongo Village faces significant gaps characterized by the absence of a Disability Service Unit (DSU), the lack of a Governor’s Regulation as a technical implementing rule, and limited accessible inclusive education facilities. These conditions result in the failure of both preventive and repressive legal protection for persons with disabilities.